PENGARUH STRATEGI ACE PADA PEMBELAJARAN FISIKA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X DI SMA NEGERI 1 PANGKAJENE - Prisuna, Bayu Fitra (EduFisika: Jurnal Pendidikan Fisika, 2020)
The purpose of this research was to know the effect of ACE strategy (Activities, Class Discussion, Exercise) toward students achievement in physics learning at SMA Negeri 1 Pangkajene. The type of this research was quasi experimental. The sample of this research was X MIA1 class as experimental class (27 students) and X MIA 2 class as the control class (27 students). The research instrument is a student learning achievement test. The hypothesis test was done with the t-test. The result showed that students achievement in physics learning at experimental class have high category, meanwhile students achievement in physics learning at control class has medium category. Based on the hypothesis test can be concluded that there are significant different between a group who was taught by using the ACE strategy and the group who was taught by using conventional learning method.